RESPONSE OF VEGETABLE LAHI (BRASSICA JUNCEA VAR. RUGOSA) TO FREQUENCY OF LEAF PICKING AND PLANT SPACING IN HILLS - PANT, TRIBHUWAN; PANDEY, M. C.; PANDEY, VANDNA; AHMED, Z. (Annals of Agricultural Research, 2014)
A field experiment was conducted at the experiment station of Defence Agricultural Research Laboratory Pithoragarh (1700 M) during the year 2003-04 and 2004-05 in Rabi season in a split plot design taking leaf picking as main plot and spacing as sub plot treatment. It was observed that maximum green leaf yield may be obtained when crop was transplanted at 30x 30 cm. spacing followed by 30 x 45 and 45 x 45 cm respectively. The leaf yield also increased with increase in number of pickings up to three. The picking did not affected the grain yield, however spacing had its significant edge in affecting the grain yield and maximum grain yield was recorded at 30 x 30 cm spacing